Embryonic heart rate is higher in species that experience greater nest predation risk during incubation - Di Giovanni, Alexander J.; Jones, Todd M.; Benson, Thomas J.; Ward, Michael P. (Ecology and evolution, 2024)
Avian eggs develop outside of the female body, and therefore embryonic development is subject to multiple internal (physiological) and external (ecological) factors. Embryonic developmental rate has important consequences for survival. Within species, embryos that develop too quickly often experience deformities, disorders, or mortality, while embryos that develop slowly risk inviability and increase the time they are exposed to various sources of mortality in the nest. These contrasting forces may lead to interspecific variation in developmental rates. We investigated potential factors affecting embryonic heart rate (EHR), a proxy of development, across 14 passerine species in the field. More specifically, we investigated if nest predation risk, clutch size, seasonality, and egg volume influenced EHR. From previous research, we expected, and found, that EHR was positively associated with embryonic age and egg temperature. Species with greater nest predation risk had higher EHR, shorter incubation periods, and lower nest temperature variance. EHR increased as the season progressed and with egg volume, while EHR declined with clutch size. Bird species exhibit varying strategies to increase nestling and fledgling survival in response to predation risk, and these results suggest that variation in embryonic development may be related to species‐specific differences in nest predation risk. We investigated potential factors affecting embryonic heart rate (EHR), a proxy of development, in 14 wild songbird species in east‐central Illinois, USA. Within species we found that EHR was positively associated with embryonic age and egg temperature, while EHR among species were positively associated with nest predation risk. Consistent with past research on avian life histories, our findings suggest that predation risk plays an important role in governing variation in EHR (and developmental rates) among songbird species.